UJI POTENSI BAKTERI DAN JAMUR PELARUT FOSFAT DALAM MENINGKATKAN JUMLAH P-TERSEDIA PADA TANAH SULFAT MASAM - Dewi R. P.; Basuki basuki; Widiastuti L. (Fakultas Pertanian Universitas Palangka Raya, 2017)
Phosphorus (P) is a nutrient required by plants for saving and transferring energy as well as a component of proteins and nucleic acids. The existence of phosphate in the soil acidic abundant may not be able be used by the plant if the phosphate is in the form is not available. This research aimed to 1). Find out potential phosphate solubilizing bacteria and fungi derived from acid sulphate soil and red-yellow podzolic soil in increasing the amount of avaibility of phosphate to the acid sulphate soil, 2) find out the difference between giving phosphate solubilizing bacteria and fungi derived from acid sulphate soils and soil podsolic yellow red in increasing the amount of phosphate available on acid sulphate soil.This study uses a completely randomized design consisting of two factors, ie phosphate solubilizing microorganism and potency test media. The results showed that first selected fungus (fungus isolates from natural rubber plantations on acid sulphate soils) suppose to beRhizopus sp were able to increase the available phosphate highest at 12,11 ppm compared to control on non-sterile media and at 20,68ppmof control on soils sterile media. Provision fungal isolates treatment derived from acid sulphate soils and red yellow podzolic soil significantly in increasing the available phosphate on acid soils non-sterile when compared to provision bacteria